2021
DOI: 10.3390/diagnostics11071209
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction in CT Torsion Measurement of the Lower Limb: Introduction of a New Ultra-Low Dose Protocol

Abstract: This study analyzed the radiation exposure of a new ultra-low dose (ULD) protocol compared to a high-quality (HQ) protocol for CT-torsion measurement of the lower limb. The analyzed patients (n = 60) were examined in the period March to October 2019. In total, 30 consecutive patients were examined with the HQ and 30 consecutive patients with the new ULD protocol comprising automatic tube voltage selection, automatic exposure control, and iterative image reconstruction algorithms. Radiation dose parameters as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…At the wrist, Neubauer et al (28) were able to show that a dose optimization has even greater potential in multi-detector CT imaging in comparison to cone beam CT, which permits a detailed bony architecture but is limited due to a smaller FOV and increased scattered radiation (29). More recently, an excellent cortical outline of bone structures in simulated ULD-CT imaging was achieved in torsion measurements of the lower limbs and the results were confirmed in real ULD-CT imaging (14,15). These findings are consistent with the results of our study indicating that ULD-CT imaging could be as accurate as high quality CT imaging of the wrist.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…At the wrist, Neubauer et al (28) were able to show that a dose optimization has even greater potential in multi-detector CT imaging in comparison to cone beam CT, which permits a detailed bony architecture but is limited due to a smaller FOV and increased scattered radiation (29). More recently, an excellent cortical outline of bone structures in simulated ULD-CT imaging was achieved in torsion measurements of the lower limbs and the results were confirmed in real ULD-CT imaging (14,15). These findings are consistent with the results of our study indicating that ULD-CT imaging could be as accurate as high quality CT imaging of the wrist.…”
Section: Discussionmentioning
confidence: 98%
“…ULD-CT simulations were generated using the raw CT data sets from the initial high quality CT with the dedicated software package ReconCT (Version 14.2.0.40998, Siemens Healthineers) similar to previous studies (14)(15)(16)(17). Simulations were made at 20%, 10%, and 5% of the original dosage and were then compared to the original data sets (100% dose level).…”
Section: Simulation Of Uld-ctmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, we developed a new ultra-low dose CT (ULD-CT) protocol with the assistance of automated tube voltage and tube current time product modulation 10,11 for patients without metal implants. Since patients who need torsion measurements of the lower limb often have metal implants, the now presented study aims to analyze the feasibility of such a ULD-CT protocol and the radiation exposure in a patient group with metal implants in the lower limb.…”
Section: Introductionmentioning
confidence: 99%
“…However, CT examinations for deep vein thrombosis and lower limb arteriosclerosis obliterans may involve a scan ranging from the torso to the lower limbs. In this case, the CTDI vol (z), Dose Length Product (DLP), and effective dose have been used as patient dose indices [9][10][11][12]. The f-factor (DLP to effective dose conversion factor) for the lower limbs is not expressed in the International Commission on Radiological Protection (ICRP) publication 102 [13], but several studies have been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%